2009
DOI: 10.1080/01674820902830276
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety among Polish infertile couples – an evaluative prevalence study

Abstract: The risk factors of depression and anxiety in infertility include: female sex, age over 30, lower level of education, lack of occupational activity, diagnosed male infertility and infertility duration of 3-6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
87
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 26 publications
14
87
3
2
Order By: Relevance
“…clinical samples) have found that levels of mental distress and symptoms of anxiety and depression are higher [1][2][3][4][5][6][7] and quality of life lower [6,[8][9][10][11] in infertile women compared with control samples without fertility problems or population norms [5,6]. Reports suggest that up to one-third of women seeking help for infertility score above cut-off values for a mental condition [1,11,12], which is similar to the prevalence of mental disorders seen in patients with somatic conditions [13].…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…clinical samples) have found that levels of mental distress and symptoms of anxiety and depression are higher [1][2][3][4][5][6][7] and quality of life lower [6,[8][9][10][11] in infertile women compared with control samples without fertility problems or population norms [5,6]. Reports suggest that up to one-third of women seeking help for infertility score above cut-off values for a mental condition [1,11,12], which is similar to the prevalence of mental disorders seen in patients with somatic conditions [13].…”
Section: Introductionmentioning
confidence: 58%
“…Mean time since start of the first unsuccessful attempt of getting pregnant was long, and the findings indicate that at the population level, and from a longitudinal perspective, the association between infertility and symptoms of depression is less pronounced than studies on women seeking help for infertility would suggest [1][2][3]7]. This study design was cross-sectional, with retrospective reports of infertility; therefore, firm conclusions about direction of causality, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…women who have never been pregnant and cannot become pregnant) were more prone to depression symptoms than women with secondary infertility (Epstein & Resenberg, 2005). Drosdzol and Skrzypulec (2009) identified the following risk factors of depression and anxiety for infertile patients: being female, age over 30, low education level, no professional activity, diagnosed male infertility, and being infertile for 3-6 years. Moreover, the author's pilot studies concerning psychological costs also revealed statistically significant differences on the basis of method and treatment time (Dembińska, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…[48] Moreover, Drosdzol et al found that 35.4% infertile women scored above the cutoff for severe symptoms of depression. [49] According to the current study findings, it was revealed that the infertile women exhibited higher statistically significant between sociodemographic variables (age, level of educational, occupational status, occupation type, age at marriage, and family income adequacy) and Psychopathology in all parameters in the form of tension, anxiety, depression. Our findings reinforce the need for gynecologists and professionals as well as health care sectors to look for psychosocial distress in women undergoing infertility treatment.…”
Section: Published By Sciedu Pressmentioning
confidence: 99%